2016
DOI: 10.1515/bnm-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear laser scanning microscopy of oral multispecies-biofilms: fixative induced fluorescence as a fast and economical in vitro screening method

Abstract: In this letter we report a fast and easy method which could be used for initial screening of multispecies-biofilm development on putative new dental implant materials. Most staining methods require numerous washing steps that can result in detachment of loosely bound biofilms and therefore falsify the results. Thus, we used glutaraldehyde fixation, which induces autofluorescence through bacterial membrane protein cross-linking and concurrently stabilizes the biofilm structure. We analyzed the biofilms with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The urea-NaCl-FISH assay was first described for Staphylococcus aureus [ 37 ]. We have already used this method in a study on the simultaneous staining of three species [ 42 ]. Our results show that urea-NaCl-FISH assay is also suitable for simultaneous FISH analysis of four different gram-positive and gram-negative bacterial species embedded in a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…The urea-NaCl-FISH assay was first described for Staphylococcus aureus [ 37 ]. We have already used this method in a study on the simultaneous staining of three species [ 42 ]. Our results show that urea-NaCl-FISH assay is also suitable for simultaneous FISH analysis of four different gram-positive and gram-negative bacterial species embedded in a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Andric et al have shown TPEF measurements with fixated bacterial biofilms can distinguish species by their respective fluorescence intensity. 7 In animal, and especially immune cells, TPEF and FLIM are being used as a non-invasive way to distinguish cells. [8][9][10][11] FLIM extends the possibilities of TPEF by measuring the temporal component of the incoming signal and can be used to distinguish between the free and bound state of the coenzymes.…”
Section: Introductionmentioning
confidence: 99%